Kompleksitas Work Life Balance (Wlb) dan Kinerja Karyawan Menuju New Normal - Honorata Ratnawati Dwi Putranti (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2020)
Background: The pandemic shows that the 19 that hit the world caused changes in all areas of the fabric of people's lives. Perceived changes, one of which is in the world of work, are causing changes in order and regulation in the field of human resource management. Aim:This study aims to create a Work Live Balance (WLB) model and flexible work of employees in the 19th era. This study uses a descriptive qualitative method with the help of questionnaires and interviews. Resource persons are employees in Indonesia with various positions and types of work. Method :study uses a data source of 200 people. from various companies throughout Indonesia by random sampling. Result :The results of this study are that men and women in the division of time have different patterns. The more women get older, the more time they can divide their time between work and social life. Men have a more dynamic graph. Some types of work and some determinations can manage the time from home, but there are types of work that must be done directly. Conclusion:The results of this study can provide input to companies in making decisions to welcome the new normal in the field of Human Resources management policies. Keywords: Covid 19; flexible work; new normal; Work life balance (WLB)